Promoção da alta performance em equipes de desenvolvimento de software no contexto de gerenciamento de projetos ágeis - Butafava, Andressa Cristina de Almeida (2023)
The competitive business environment that we are experiencing today requires a multitude of companies to maintain organizational results. As a support to organizational strategy, project management has come to be seen as a competitive advantage for companies. Although several factors can contribute to the success of these companies, part of the solution lies in improving the work team. Thus, the allocation of people by skills is essential to enhance productivity and the value delivered by companies. In this sense, high-performance teams represent a key element in achieving the strategic expectations of senior management. These teams have clear goals, invest time and effort to create purposes that individually and collectively meet their aspirations, as the teams are result-oriented and have a leadership that supports and encourages its members. Based on what was presented, this dissertation aimed to describe how to promote high performance in software development teams in the context of agile project management. Regarding the methodological procedures, a qualitative strategy was applied to construct a multicase study using group meetings, participant observation, semi-structured interviews and document analysis. The first part of the research started with the execution of a systematic literature review that was carried out in order to enable the construction of the conceptual model developed and its validation. From this initial study, the methodological procedures were divided into four stages, namely: (i) Conception, (ii) kick-off, (iii) Application and (iv) Model refinement and final report. The results of this research comprise the construction of a model based on macro categories and their respective attributes, including the addition of the product vision attribute. In addition, the model evolved from the empirical validation process includes the macro categories and the performance plan that describe a process of developing high-performance teams. This research contributes to the promotion of high performance in software development teams that work in the context of an agile management approach. The conceptual model applied in the three different teams validates, through the construction of performance plans, retrospective sessions and monitoring of indicators, the promotion of high performance. This research is aligned with research line 2 (Project Management) linked to the Graduate Program in Project Management – PPGP UNINOVE. This dissertation is also in line with other researches by his advisor linked to the axis project “People Management and Project Management”.